Strong Mixing and Recirculation in the Northwestern Argentine Basin - Valla, Daniel (2018)
The Atlantic component of the Meridional Overturning Circulation (AMOC) is a key contributor to the global meridional transport of volume, salt, and heat, and thus plays a central role in global climate. As part of ongoing efforts to monitor the intensity and variability of the AMOC in the South Atlantic, hydrographic sections have been regularly occupied since 2009 near the western boundary along a zonal line at 34.5°S. Here this high-quality, high-resolution data set is analyzed to establish the average hydrographic conditions of the northwestern Argentine Basin and the water mass spatial and temporal variability. The water mass analysis also reveals the pathways of the flow in this region, which are further corroborated by full-depth direct velocity measurements. The repeated hydrographic sections capture an extremely rich vertical structure, characterized by seven distinct water mass layers of northern and southern origin, each with unique property signatures. Almost all of these layers exhibit a sharp zonally banded structure, which is indicative of recirculation cells offshore from the western boundary. The circulation at intermediate levels includes a previously undetected recirculation cell confined very close to the western boundary and superimposed on the classical intermediate water pathway beneath the South Atlantic subtropical gyre. The deep level flow is characterized by the Deep Western Boundary Current (DWBC) and a northward recirculation ~500 km east from the slope.